Pengaruh Pendidikan Kesehatan dengan Booklet terhadap Pengetahuan Remaja Putri tentang Anemia di SMA Negeri Kabupaten Landak - Angelina, Putri Tiara; Navelia, Zesika Intan; Fadhilah, Siti Intan (Poltekkes Kemenkes Palembang, 2025)
Background: Anemia refers to a condition where the number of red blood cells or the concentration of hemoglobin is below normal. According to the profile of the Ministry of Health of the Republic of Indonesia, anemia is the most commonly encountered health problem worldwide, particularly in developing countries. Female adolescents are at a higher risk of developing anemia. The anemia status among adolescents is also associated with their level of knowledge. One method to improve female adolescents; knowledge about anemia is through health education in the form of counseling using booklets, aimed at determining the effect of health education with booklets on the knowledge of female adolescents about anemia at SMA Negeri 1 Banyuke Hulu. Research Method: This study used a quasi-experimental method with a pretest- posttest design with a control group applied to two groups. The total sample consisted of 60 respondents selected using the simple random sampling method. Data were collected using a questionnaire, and the data were analyzed using the paired t-test. Results: The statistical test showed a difference in the average knowledge scores of students between the pretest and posttest. The mean posttest score in the group receiving health education using booklet media was 87.33, while the mean posttest score in the group receiving lecture-based education was 69.66. The group of students who received counselling through booklet media showed a significant difference between the pretest and posttest scores, indicating a significant effect of booklet-based health education on female adolescents’ knowledge about anemia. This implies that health education using booklets had an effect on increasing the knowledge of female adolescents about anemia at SMAN 1 Banyuke Hulu. Conclusion: The p-value of 0.000 < 0.05 indicates that health education using booklets has a significant effect on increasing the knowledge of female adolescents about anemia at SMAN 1 Banyuke Hulu.